ПРОЕКТНА ДІЯЛЬНІСТЬ ЯК ЗАСІБ СОЦІАЛЬНО- ПРОФЕСІЙНОЇ АДАПТАЦІЇ СТУДЕНТІВ ДО ВИХОВНОЇ РОБОТИ В ШКОЛІ (Педагогіка вищої та середньої школи, 2022)
In article the author gives an example of independent prosecution of students of realization of creative pedagogical project on theme: “Program of organization of life ofpupil elder classes ”.